Monoclonal antibody characterization of the C proteins of heterogeneous nuclear ribonucleoprotein complexes in vertebrate cells (The Rockefeller University Press, 1984)
The C proteins (C1 and C2) are major constituents of the 40S subparticle of heterogeneous nuclear ribonucleoprotein complexes (hnRNPs) (Beyer, A.L., M.E. Christensen, B.W. Walker, and W.M. LeStourgeon, 1977, Cell, 11:127-138) and are two of the most prominent proteins that become cross-linked by ultraviolet light to heterogeneous nuclear RNA (hnRNA) in vivo. Studies are described here on the characterization of the C proteins in vertebrate cells using monoclonal and polyclonal antibodies. Monoclonal antibodies to genuine RNP proteins, including the C proteins, were obtained by immunizing mice with purified complexes of poly(A)+ hnRNA and poly(A)+ mRNA with their contacting proteins in vivo obtained by ultraviolet cross-linking the complexes in intact cells (Dreyfuss, G., Y.D. Choi, and S.A. Adam, 1984, Mol. Cell. Biol., 4:1104-1114). One of the monoclonal antibodies identified the C proteins in widely divergent species ranging from human to lizard. In all species examined, there were two C proteins in the molecular weight range of from 39,000 to 42,000 for C1, and from 40,000 to 45,000 for C2. The two C proteins were found to be highly related to each other; they were recognized by the same monoclonal antibodies and antibodies raised against purified C1 reacted also with C2. In avian, rodent, and human cells the C proteins were phosphorylated and were in contact with hnRNA in vivo. Immunofluorescence microscopy demonstrated that the C proteins are segregated to the nucleus. Within the nucleus the C proteins were not found in nucleoli and were not associated with chromatin as seen in cells in prophase. These findings demonstrate that C proteins with similar characteristics to those in humans are ubiquitous components of hnRNPs in vertebrates.